The effect of green technology policy on climate change awareness of youth in Sabah, Malaysia - Sarimah Surianshah; Suriani Hassan; Audrey Liwan (Penerbit Akademia Baru, 2024)
The role to mitigate climate change issue should be embark among youth. This study examines the effects of green technology policy on climate change awareness of youth in Sabah, Malaysia. Using a random sampling method, this study involved 254 respondents from four areas of Sabah namely Tawau, Lahad Datu, Sandakan, and Kota Kinabalu. This study used two approaches which are i) probit model and ii) two-stage least squares method. We find a positive effect between youth’ positive perceptions on green technology policy on their climate change awareness. In addition, the effect becomes five times higher when we address the endogeneity problem in model estimation using the two-stage least squares method and identification strategy based on the prospect theory. This study has highlighted the great impact of youth in implementing green technology to reduce climate change issues in Malaysia in general.